2020
DOI: 10.2337/figshare.13148381.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Durability of Triple Combination Therapy Versus Stepwise Addition Therapy in Patients With New-Onset T2DM: 3-Year Follow-up of EDICT

Abstract: <b>Objective:</b> To compare the long term efficacy of initiating therapy with metformin/pioglitazone/exenatide in new onset T2DM patients versus sequential addition of metformin followed by glipizide and insulin. <p><b>Research Design and</b> <b>Methods</b>: 318 drug naïve, new onset T2DM were randomized to receive for 3 years: (1) combination therapy with metformin/pioglitazone/ exenatide (Triple Therapy) or (2) sequential addition of metformin followed by glipizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Previous studies provided evidence that longterm durable glycemic control can decrease the incidence of diabetic complications [5]. Although previous studies have suggested the potential benefit of early intensive glucose-lowering therapy, most of the current practice guidelines recommend serial escalation of diabetic medications in patients with newly diagnosed diabetes unless those patients are severely hyperglycemic [6,7]. The optimal duration to target glycosylated hemoglobin (HbA1c) achievement and its potential benefits in a clinical setting are poorly understood.…”
mentioning
confidence: 99%
“…Previous studies provided evidence that longterm durable glycemic control can decrease the incidence of diabetic complications [5]. Although previous studies have suggested the potential benefit of early intensive glucose-lowering therapy, most of the current practice guidelines recommend serial escalation of diabetic medications in patients with newly diagnosed diabetes unless those patients are severely hyperglycemic [6,7]. The optimal duration to target glycosylated hemoglobin (HbA1c) achievement and its potential benefits in a clinical setting are poorly understood.…”
mentioning
confidence: 99%
“…For example, although first line therapy with metformin may provide acceptable metabolic control early in the course of the disease, it is often necessary to add one or more drugs to restore acceptable metabolic control 1,2,16,17 . Physicians have quite a number of options when selecting a second drug to prescribe for patients who are inadequately controlled on metformin monotherapy -including, DPP4 inhibitors, SGLT2 inhibitors, GLP1R agonists, sulfonylureas, and pioglitazone among others 1,2,17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…The study protocol was approved by the Institutional Review Board of University of Texas Health Science Center at San Antonio and informed written consent was obtained from all participants before enrolment. The study design 18 and primary outcome 19 have been published. Briefly, drug‐naïve, new‐onset (<2 years) T2D patients, age 18‐75 years, who otherwise were healthy, were recruited into the study.…”
Section: Methodsmentioning
confidence: 99%
“…15 Thus, including a TZD in glucose-lowering therapy, which is the only true insulin sensitizer available, will address both the major core defects of T2D, beta cell dysfunction and insulin resistance. 15 The Efficacy and Durability of Initial Combination Therapy for Type 2 Diabetes (EDICT) study 18,19 compared the efficacy of two glucose-lowering therapeutic strategies in newly diagnosed T2D patients: (a) initiation of triple therapy with metformin plus pioglitazone plus GLP-1 RA at the time of diagnosis versus (b) initiation of therapy with metformin followed by sequential addition of sulphonylurea followed by basal insulin to maintain the HbA1c at less than 6.5%. Because there was no upper limit for HbA1c inclusion, 104 study participants had an initial HbA1c of more than 10% and all manifested weight loss in the preceding months.…”
mentioning
confidence: 99%